Detection of tuberculosis: respiratory symptoms flow and results achieved - Lílian Moura de Lima Spagnolo; Jéssica Oliveira Tomberg; Dagoberta Alves Vieira; Roxana Isabel Cardozo Gonzales
ABSTRACT Objective: to analyze the flow of care to the person with symptoms of tuberculosis and the results achieved in the detection of cases in Primary Health Care units of two municipalities of Rio Grande do Sul. Method: descriptive of mixed methods, developed between 2013 and 2016. We used secondary data of 69 units and semi-structured interviews with 10 professionals. Descriptive statistical analysis and content analysis were used. Results: it was observed that the fragmented flow of attention to the respiratory symptoms in Pelotas resulted in low detection of cases by Primary Care, 8.8% of the diagnoses of the municipality. The Sapucaia do Sul flow presents continuity of care, and Primary Care performed 50% of the diagnoses of the municipality. Conclusion: the organization of flows by municipal management was instrumental in promoting or limiting the commitment of Primary Health Care teams in coordinating care and consequently in achieving the goals of disease control.